Magnetostructural coupling induced magnetocaloric effects in Ni–Mn-Ga-Fe microwires. (September 2019) - Liu, Yanfen; Luo, Lin; Zhang, Xuexi; Shen, Hongxian; Liu, Jingshun; Sun, Jianfei; Zu, Ningning
Abstract: Ferromagnetic shape memory Ni–Mn-Ga alloys exhibit magnetostructural coupling during the Curie points, which may alter their magnetocaloric effect (MCE). Here MCE of Ni–Mn-Ga alloy microwires are tuned by Fe-doping. The chemical ordering annealed Ni49·6 Mn25.5 Ga22.6 Fe2.3 (Fe2), Ni49·6 Mn25 Ga21 Fe4.4 (Fe4) and Ni48 Mn26 Ga19.5 Fe6.5 (Fe6) microwires have diameters of ~30–50 μm and grain sizes of ~2–5 μm. The magnetic entropy changes (Δ S m ) of the microwires increase with external magnetic fields, then reach a positive peak and finally decrease to negative peak at a high field. The direct (negative Δ S m, DMCE) and inverse (positive Δ S m, IMCE) MCEs are attributed to microscopic and mesoscopic couplings in microwires. In addition, the specific features of MCEs are also controlled by the magnetization difference (Δ M ) between martensite and austenite phases. Interestingly, the DMCE and IMCE are component dependent. At high Δ M, the linearly decreasing region is dominant and Fe4 and Fe6 microwires produce a negative Δ S m at high magnetic fields due to the microscopic coupling with free electron valence ratio e / a  = 7.692 and 7.725. On the other hand, the Δ M is small in Fe2 microwire, which has a positive Δ S m because mesoscopic coupling is dominant with e / a  = 7.607; the Δ S m is highest when a single variant martensite occurs, then decreases linearly with increasing magnetic fields. The transition from positive to negative values in Δ S m with the applied fields is related to the counterbalance of mesoscopic and microscopic couplings at e / a  = 7.66. Graphical abstract: The study found that, the specific features of the MCE in the present Ni–Mn-Ga-Fe microwires have been found to be controlled by the magnetization difference between martensite/austenite phases (Δ M  =  M M - M A ). At small Δ M, the ΔS m is first positive, reaches a maximum under a critical magnetic field (e.g. 7.6 kOe for Fe2 where a single variant martensite state occurs), and decreases linearly with H for higher fields. For high values of Δ M, the linearly decreasing region is dominant (e.g. Fe6).Image 1 Highlights: Ni–Mn-Ga-Fe microwires with fine grains were fabricated by melt-extraction. The mixed direct and inverse MCEs caused by the magnetostructural coupling. The MCE can be adjusted by changing the content of Fe.